Worker Protection Standard: Information at a Central Location - Frederick M. Fishel (EDIS)
The Agricultural Worker Protection Standard (WPS) is a federal regulation designed to protect agricultural workers (people involved in the production of agricultural plants) and pesticide handlers (people mixing, loading, or applying pesticides or doing other tasks involving direct contact with pesticides). It has been in full implementation since 1995. This document is PI-112, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date March 2006.